A thermostable presentation of the live, attenuated peste des petits ruminants vaccine in use in Africa and Asia - Mariner, Jeffrey C.; Gachanja, J.; Tindih, H.S.; Toye, Philip G. (Elsevier, 2017)
The research objective was to develop a thermostable vaccine against peste des petits ruminants (PPR), a morbilliviral disease of small ruminants targeted for eradication that is a major constraint on the livelihoods of the rural poor throughout much of Africa and Asia. Although existing PPR vaccines provide life-long immunity, they require continuous refrigeration. This limits their utility in developing countries. Methods for the lyophilization of a related morbillivirus, rinderpest (RP), resulted in vaccine that could be used in the field for up to 30 days without refrigeration which was a major contribution to the global eradication of RP completed in 2011. The present research applied the rinderpest lyophilization method to the attenuated Nigeria 75/1 PPR vaccine strain, and measured thermostability in accelerated stability tests (AST) at 37 °C. The shelf-life of the vaccine was determined as the time a vial retained the minimum dose required as a 25-dose presentation at the specified temperature. A lactalbumin hydrolysate and sucrose (LS) stabilizer was compared to stabilizers based on trehalose. PPR vaccine produced using the Xerovac drying method was compared to vaccine produced using the rinderpest lyophilization method in AST. LS vaccine was evaluated in AST at 37, 45 and 56 °C and an Arrhenius plot was constructed for estimation of stability at temperatures not tested. Vaccines produced using LS and the rinderpest method of lyophilization were the most stable. The shelf-life of the Xerovac preparation was 22.2 days at 37 °C. The three LS vaccine batches had shelf-lives at 37 °C of 177.6, 105.0 and 148.9 days, respectively, at 37 °C. At 56 °C, the shelf-life was 13.7 days. The projected half-life at 25 °C was 1.3 years. This is sufficient thermostability for use without a cold chain for up to 30 days which will greatly facilitate the delivery of vaccination in the global eradication of PPR.